Length-weight relationships of Acetes spp. sampled along the west coast of Peninsular Malaysia - Boon, Yee Wong; Han, Kiat Alan Ong; Gideon, Khoo (Universiti Kebangsaan Malaysia, 2015)
The present study describes the length-weight relationships (LWRs) of four Acetes species (Acetes indicus, A. serrulatus, A. japonicus and A. sibogae) which were sampled from offshore trawling and inshore catches along the west coast of Peninsular Malaysia. Morphometric measurements (total length, TL and wet weight, WW) were obtained from the samples and LWRs were estimated. All LWRs were significant (p<0.05) for the four species, with the coefficient of determination, R2> 0.659. The estimated b values for LWR were 2.432-3.403. The R2 value was >0.84 when the data was analysed according to inshore and offshore samples. Male and female A. indicus and A. serrulatus demonstrated negative allometric growth whilst male A. japonicus and A. sibogae showed isometric growth type. Positive allometric growth was depicted by a combined group of male and female A. sibogae. This study has contributed to the knowledge of the offshore and inshore distribution patterns of different populations of Acetes spp. in the Straits of Malacca. It also presents a comparison of the LWRs between offshore and inshore catches of A. indicus and A. serrulatus, with the inshore catches of A. japonicus and A. sibogae, which have not been previously reported. The findings of this study would contribute to the conservation and management of this commercially important fisheries resource.